0313 The Role of Objective Sleep on Subjective and Objective Cognition in Older Adults with Insomnia: A Pilot Study. (25th May 2022) - Costa, Amy; Musich, Madison; Knous, Dakota; McCrae, Christina; Cowan, Nelson; Curtis, Ashley
Abstract: Introduction: Cognitive complaints and objective cognitive dysfunction are common in aging populations, but findings regarding associations between them are inconclusive. Given age-related sleep changes [more lighter-staged sleep, reduced sleep efficiency (SE)], and known relationships between insomnia complaints and cognitive dysfunction, this pilot tested whether polysomnographic sleep moderates associations between subjective and objective cognition in older adults with insomnia complaints. Methods: Older adults with insomnia complaints (N=37, Mage=68.9, SD=6.23, 20 women) completed one night of polysomnography (Sleep Profiler-PSG2TM) and the NIH Toolbox [Pattern Comparison (processing speed), Dimensional Change Card Sort (cognitive flexibility), Stroop (attention and inhibition), and Sternberg (working memory). Additionally, participants completed the Cognitive Failures Questionnaire (subscores CFQ-memory, CFQ-distractibility CFQ-blunders computed). Multiple regressions examined if polysomnographic sleep (SE, %N1, %N3) moderated associations between subjective/objective cognition, controlling for apnea-hypopnea index and depression. Results: %N1 moderated associations between Sternberg performance and CFQ-memory (R2=.13, p=.03), CFQ-distractibility (R2=.20 p=.01) and CFQ-blunders (R2=.19 p=.02). At highest %N1, worse working memory was associated with less complaints in memory (β=16.4, p=.03), distractibility (β=12.4, p=.009) and blunders (β=15.3, p=.02). Additionally, %N1 (R2=.14, p=.02) and SE (R2=.17, p=.02) moderated the association between dimensional change performance and CFQ-distractibility. At lowest %N1, worse cognitive flexibility was associated with more distractibility complaints (β=-988.8, p=.02), while at highest %N1, worse cognitive flexibility was associated with less distractibility complaints (β=3881.4, p=.02). At lowest SE, worse cognitive flexibility was associated with less distractibility complaints (β=2354.0 p=.02), while at highest SE, worse cognitive flexibility was associated with more distractibility complaints (β=-1414.1 p=.03). Conclusion: Preliminary findings suggest in older adults with insomnia complaints, greater time spent in lighter-staged sleep and more sleep fragmentation may exacerbate discrepancies in the objective/subjective cognition relationship, while less time spent in lighter-staged sleep and less sleep fragmentation may converge the objective/subjective relationship. Objective sleep should be considered when understanding discrepancies between subjective reports versus neuropsychological/objective cognition profiles. Prospective studies with larger samples examining how sleep impacts the trajectory of subjective/objective cognition in aging are warranted. Support (If Any): This research was made possible by an award (PI:Curtis) from the American Academy of Sleep Medicine Foundation, a foundation of the American Academy of Sleep Medicine.